2013
DOI: 10.1007/s10096-013-2011-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic analysis of Vibrio cholerae non-O1, non-O139 isolated from German and Austrian patients

Abstract: Vibrio cholerae belonging to the non-O1, non-O139 serogroups are present in the coastal waters of Germany and in some German and Austrian lakes. These bacteria can cause gastroenteritis and extraintestinal infections, and are transmitted through contaminated food and water. However, non-O1, non-O139 V. cholerae infections are rare in Germany. We studied 18 strains from German and Austrian patients with diarrhea or local infections for their virulence-associated genotype and phenotype to assess their potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 42 publications
3
79
0
1
Order By: Relevance
“…For example, Lasch et al (2014) (20) and Schirmeister et al (2013) reported the same for Vibrio cholerae isolates (21) and such studies may represent the tip of the difficult-to-publish iceberg. After examination of successful reports on MALDI-TOF MS typing, it becomes evident that for some bacterial taxa, the available data are not consistent.…”
Section: Typing By Maldi-tof Ms: What Can We Learn From Pfge?mentioning
confidence: 99%
“…For example, Lasch et al (2014) (20) and Schirmeister et al (2013) reported the same for Vibrio cholerae isolates (21) and such studies may represent the tip of the difficult-to-publish iceberg. After examination of successful reports on MALDI-TOF MS typing, it becomes evident that for some bacterial taxa, the available data are not consistent.…”
Section: Typing By Maldi-tof Ms: What Can We Learn From Pfge?mentioning
confidence: 99%
“…However, infections other than cholera can be caused by nonepidemic V. cholerae serogroups that are collectively referred to as non-O1/non-O139 V. cholerae and are generally acquired through the consumption of raw or undercooked seafood. Non-O1/non-O139 V. cholerae infections are continuously reported worldwide (3,4), emphasizing their clinical significance. Although non-O1/non-O139 V. cholerae strains generally do not produce cholera toxin, other virulence factors contribute to their pathogenicity, including the hemolysin gene hlyA (5), the protease gene hapA (6), the cytotoxic actin cross-linking repeats in toxin gene rtxA (7), the sialidase gene nanH (8), the heat-stable toxin (NAG-ST) (9), a type 6 secretion system (T6SS) (10), and a type 3 secretion system (T3SS) (11).…”
mentioning
confidence: 99%
“…Furthermore, Shiga toxin E. coli, Salmonella serotypes, C. difficile ribotypes and Vibrio cholera phenotypes have also been identified [51][52][53][54][55].…”
Section: Species Identification In 3 H Culturementioning
confidence: 99%